2020
DOI: 10.3390/biom11010030
|View full text |Cite
|
Sign up to set email alerts
|

Iron Dysregulation and Inflammagens Related to Oral and Gut Health Are Central to the Development of Parkinson’s Disease

Abstract: Neuronal lesions in Parkinson’s disease (PD) are commonly associated with α-synuclein (α-Syn)-induced cell damage that are present both in the central and peripheral nervous systems of patients, with the enteric nervous system also being especially vulnerable. Here, we bring together evidence that the development and presence of PD depends on specific sets of interlinking factors that include neuroinflammation, systemic inflammation, α-Syn-induced cell damage, vascular dysfunction, iron dysregulation, and gut … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(31 citation statements)
references
References 254 publications
(364 reference statements)
0
31
0
Order By: Relevance
“…In this review, we discussed the link between the BBB disruption and the occurrence of SAE, aiming at finding novel strategies to treat SAE by maintaining the barrier function of BBB. Systemic injection of LPS has been shown to cause damage to the BBB of recipient animals, resulting in the subsequent entry of peripheral cytokines into the brain ( Vuuren et al, 2020 ). It is believed that the main contribution of the damaged BBB to the occurrence and development of SAE is to cause a large number of inflammatory factors and neurotoxins to enter the brain tissue, accompanied by immune cells in the brain tissue such as microglia being activated during systemic inflammation, thereby mediating neuroinflammation and oxidative stress.…”
Section: Discussionmentioning
confidence: 99%
“…In this review, we discussed the link between the BBB disruption and the occurrence of SAE, aiming at finding novel strategies to treat SAE by maintaining the barrier function of BBB. Systemic injection of LPS has been shown to cause damage to the BBB of recipient animals, resulting in the subsequent entry of peripheral cytokines into the brain ( Vuuren et al, 2020 ). It is believed that the main contribution of the damaged BBB to the occurrence and development of SAE is to cause a large number of inflammatory factors and neurotoxins to enter the brain tissue, accompanied by immune cells in the brain tissue such as microglia being activated during systemic inflammation, thereby mediating neuroinflammation and oxidative stress.…”
Section: Discussionmentioning
confidence: 99%
“… 6 In addition, the contents of metal elements (e.g., iron, copper, zinc and manganese) in cerebrospinal fluid and brain of patients with PD are much higher than normal ones. Excessive metal concentration involved in the oxidative damage to neuron cells, 3 , 4 particularly iron ions, which react with hydrogen peroxide to generate hydroxyl radicals. 38 The increase of free radicals generates lipid peroxidation, which causes the member damage and cell degeneration.…”
Section: Discussionmentioning
confidence: 99%
“…9 , 10 These abnormal metal elements can cause oxidative damage to dopaminergic neuron cells. 3 , 4 , 7 , 9 Therefore, antioxidant therapy has become one of the treatments of PD. Some drugs have antioxidant neuroprotective effects, can delay the progress of the symptoms of PD in the experimental study, 11 , 12 , 13 , 14 but they still have not proven to be clinically safe or effective.…”
Section: Introductionmentioning
confidence: 99%
“…However, they can adopt an ominous function and recent studies have shown an association between gut microbiota and neurological disorders (Gorle et al 2021 ). In fact, there are reports suggestive of peripheral inflammation which is prompted by bacterial derived inflammagens which consequently spreads to the brain (Vuuren et al 2020 ). This may play a key role in the development of PD.…”
mentioning
confidence: 99%
“…By virtue of eliciting rogue immune reactions, they have the potential in collaboration with other features to unleash deadly pathomechanisms characteristic of the disorder. Indeed, factors such as, α-synuclein aggregates, inflammation in the enteric nervous system and brain, iron elevation in the SN and a disruption of gut flora by some pathogen may contrive to elicit the characteristic neurodegeneration exhibited in the disease (Vuuren et al 2020 ). It therefore may be prudent to explore more carefully the pathways/processes elicited by these pathogens as it may lead to the aetiology of the illness or provide a better understanding of the underlying pathogenesis of PD.…”
mentioning
confidence: 99%